Overpricing persistence in experimental asset markets with intrinsic uncertainty - Didier Sornette; Sandra Andraszewicz; Ke Wu; Ryan O. Murphy; Philipp Rindler; Dorsa Sanadgol (Kiel Institute for the World Economy (IfW), 2019)
To study coordination in complex social systems such as financial markets, the authors introduce a new prediction market set -up that accounts for fundamental uncertainty. Nonetheless, the market is designed so that its total value is known, and thus its rationality can be evaluated. In two experiments, the authors observe that quick consensus emerges early yielding pronounced mispricing, which however do not show the standard "bubble -and -crash". The set -up is implemented within the xYotta collaborative platform (https://xyotta.com). xYotta's functionality offers a large number of extensions of various comple xity such as running several parallel markets with the same or different users, as well as collaborative project development in which projects undergo the equivalent of an IPO (initial public offering) and whose subsequent trading matches the role of financial markets in determining value. xYotta is thus offered to researchers as an open source software for the broad investigation of complex systems with human participants.
Keywords: C90; D47; D80; 330; experimental asset market; predicion market; uncertainty; experimental economics